Piracy, Maritime Terrorism and Securing the Malacca Straits - Ong-Webb, Graham Gerard (Book collections on Project MUSE., 2006)
Maritime piracy continues to persist as a significant phenomenon, revealing a range of social, historical, geo-political, security, and economic issues. Today, the waters of Southeast Asia serve as the dominant region for the occurrence of piracy and the challenges it poses to regional security and Malacca Straits security in particular. As a second instalment within the Series on Maritime Issues and Piracy in Asia by the International Institute of Asian Studies, Leiden University, and the Institute of Southeast Asian Studies, the authors of this volume add fresh perspectives to the ongoing debate about piracy, the threat of "maritime terrorism", and the challenge of securing the Malacca Straits today.